Effectiveness of Physical Activity Interventions on Cognition, Neuropsychiatric Symptoms, and Quality of Life of Alzheimer’s Disease: An Update of a Systematic Review and Meta-Analysis - Liang, Ya-Jing; Su, Qing-Wen; Sheng, Zhi-Ren; Weng, Qiu-Yan; Niu, Yan-Fang; Zhou, Hong-Di; Liu, Chun-Bo (Frontiers in Aging Neuroscience, 2022)
The topic of physical activity interventions for the treatment of Alzheimer's disease (AD) has been discussed for decades, but there are still inconsistent views on the effect of its intervention in different studies. With the increase in randomized controlled trials (RCTs), it is necessary to update newly published studies and systematically evaluate the effects of physical activity interventions. Scientific citation databases (e.g. PubMed, EMBASE, etc.) and registration databases (e.g. ISRCTN, CHICTR, etc.) were checked to screen RCTs and systematic reviews of physical activity interventions in AD. Then extract and review the intervention methods and their evaluation results in the included studies. Spearman correlation method was used to test the association between the mean difference (MD) of intervention results and activity time. The Hedges’g method was used to combine continuous data to analyze the standard MD (SMD) of different intervention types or time subgroups. The overall results show that physical activity intervention can improve the cognition, neuropsychiatric symptoms and quality of life (Qol) of AD patients, but the duration of the intervention significantly affected the outcome of the assessment. Subgroup analysis results showed that an intervention duration of 2-5 months had a significant advantage: cognitive function (Minimum Mental State Examination: SMD = 0.47, 95% CI = 0.33 ~ 0.61, P < 0.01), neuropsychiatric symptoms (Neuropsychiatric Inventory: SMD = -0.48, 95% CI = -0.85 ~ -0.11, P < 0.01), and quality of life (Qol-AD: SMD = 0.47, 95% CI = 0.23 ~ 0.71 , P < 0.01). The systematic review and analysis results of updated RCTs suggested that short-term (2-5 months) physical activity interventions were more beneficial in improving cognitive function, neuropsychiatric symptoms and Qol in patients with AD. And there was no evidence of differences in the effectiveness of different physical activity interventions.